(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The article examines the key advantages and challenges of inclusive education in modern schools. The theoretical foundations of inclusion, international and national experience in implementing inclusive practices are analyzed. Special attention is paid to the barriers faced by teachers, parents, and students, as well as possible ways to overcome them. As a result of the research, recommendations have been proposed for improving inclusive education, aimed at increasing its effectiveness and accessibility.